Heterotopic ossifications and Charcot joints: Congenital insensitivity to pain with anhidrosis (CIPA) and a novel NTRK1 gene mutation - Guchev Z; Tasic V; Bogevska I; Laban N; Saveski A; Polenakovic M; Plaseska-Karanfilska D; Komlosi K; Winter J; Schweiger S; Nishimura G; Spranger J; et al. (Elsevier BV, 2020)
Congenital insensitivity to pain with anhidrosis (CIPA), also known as hereditary sensory and autonomic neuropathy type IV (HSAN-IV), is a rare and severe autosomal recessive disorder. We report on an adult female patient whose clinical findings during childhood were not recognized as CIPA. There was neither complete anhidrosis nor a recognizable sensitivity to heat. Tumorlike swellings of many joints and skeletal signs of Charcot neuropathy developed in adolescence which, together with a history of self-mutilation, led to a clinical suspicion of CIPA confirmed by identification of a novel homozygous variant c.1795G > T in the NTRK1 gene in blood lymphocytes. Both parents were heterozygous for the mutation. The variant predicts a premature stop codon (p.Gly599Ter) and thus represents a pathogenic variant; the first reported in the Southeastern European population.